Comparison of robot-assisted single-port-plus-one pyeloplasty vs. laparoscopic single-port pyeloplasty in the treatment of ureteropelvic junction obstruction in children - Li, Jun; Chen, Jingyi; Jia, Jinfu; He, Shaohua; Xu, Di (Frontiers in Pediatrics, 2024)
Objective To compare the efficacy of robot-assisted single-port-plus-one pyeloplasty (RSPY) and laparoscopic single-port pyeloplasty (LSPY) in the treatment of children with ureteropelvic junction obstruction (UPJO). Methods The clinical data of 47 children who underwent surgery for UPJO at the Department of the Pediatric Surgery of the Fujian Provincial Hospital from October 2020 to September 2022 were analyzed retrospectively. Of these 47 children, 27 received RSPY while 20 underwent LSPY. The baseline data, operation time, intraoperative anastomosis time, intraoperative blood loss, postoperative hospital stay, complications, total cost, preoperative and postoperative renal parenchymal thickness (PT), anteroposterior renal pelvis diameter (APD), and differential renal function (DRF) of the two groups were compared to evaluate the clinical efficacy of the two surgical methods. ResultsThe results showed that both surgical techniques were successful and no patient transitioned to open surgery. There was no significant difference between the two groups in baseline data, intraoperative blood loss, complications, APD, and PT 6 months after surgery. There was also no significant difference in APD, PT, and DRF 12 months after surgery (all P > 0.05). Compared with the LSPY group, the RSPY group had shorter operation time [(153.04 ± 14.44) vs. (189.90 ± 32.59) min, t = -5.24, P < 0.05], less intraoperative anastomosis time [(68.81 ± 16.80) vs. (97.45 ± 11.99) min, t = -6.49, P < 0.05], shorter postoperative hospital stay [(5.96 ± 1.34) vs. (9.00 ± 1.33) d, t = -7.68, P < 0.05], but higher total cost [(57390 ± 7664) vs. (30183 ± 4219) yuan, t = 14.32, P < 0.05]. Conclusion Compared with LSPY, RSPY achieves equivalent efficacy in the treatment of UPJO in children and has certain advantages by shortening the operation time, intraoperative anastomosis time, and postoperative hospital stay. However, its cost burden is heavy, and appropriate cases need to be selected for popularization and application.